Strategi Pemasaran Berbasis Preferensi Konsumen untuk Pengembangan Usaha Tempe di Kabupaten Tana Toraja Sulawesi Selatan - Aguinalty Sofia Rante Allo; Sumange, La; Syamsinar Syamsinar (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Initial survey results show that consumers in the Makale region have specific preferences for tempeh packaging and quality, but business actors have not incorporated these preferences into their production and marketing strategies. This gap calls for an intervention to develop a strategy based on a systematic, contextual mapping of consumer preferences. Using a mixed methods approach with an explanatory sequential design, the study was conducted in two stages: first, quantitative data collection and analysis, followed by qualitative data collection and analysis to clarify and deepen the results. The study found that consumer preferences for Jeslyn tempeh are primarily influenced by sensory qualities (taste, texture, aroma), cleanliness, affordability, hygienic packaging, distribution ease, and promotion. The Likert scale analysis showed that most indicators had an average value above 4.20 (percentage index > 84%), indicating high to very high consumer satisfaction. Taste (mean 4.52; index 90.4%) and texture (mean 4.44; index 88.8%) were the most influential factors, followed by price and cleanliness. Consumer loyalty is built through consistent quality and emotional attachment to local products. Producers should maintain product quality, improve hygiene, introduce simple innovations, and use social media for cost-effective promotion.